Basic Life Support for Elderly Caregivers at Griya Lansia Jannati, Gorontalo Province - Pipin Yunus; Rona Febriyona; Halidun Rauf; Lisatriani Kude; Siti Nursela Pulogu (Journal of Universal Community Empowerment Provision, 2021)
This service aims to serve as an understanding for the community in carrying out basic life support to reduce the occurrence of deaths caused by delays and inaccuracies in first aid. The service was carried out at Griya Lansia Jannati, Gorontalo Province. The sample amounted to 16 respondents. Techniques and Methods of Implementation using Pre-Test and Post-Test. pre-test and post-test questionnaires given to training participants to determine community understanding before and after being given Basic Life Support training. Analysis of the data obtained an assessment of the increase in knowledge before and after treatment using the Descriptive Static test. The results at the pre test were in the good category 37.5%, and the less category was 62.5% and the results at the post test were in the good category 68.8% and less category 31.3%. Based on the results of the training, it was shown that most of the elderly caregivers stated that this training was very useful because they gained knowledge and understanding of Basic Life Support. The results of the study there was an increase in knowledge before and after counseling, Conclusion: There was an increase in knowledge after counseling about Basic Life Support